Research activity and capacity in primary healthcare: The REACH study: A survey - Glynn, Liam G (BioMed Central, 2009)
BACKGROUND: Despite increased investment in primary care research and development (R&D), the level of engagement of primary healthcare professionals with research remains poor. The aim of this study is to assess the level of research activity and capacity for research among primary healthcare professionals in a health authority of over one million people in a mixed urban/rural setting in the West of Ireland. METHODS: A questionnaire, incorporating the R+D Culture Index, was sent to primary healthcare professionals in the HSE Western Region. Baseline characteristics were analysed with the use of one-way ANOVA and Chi-square test and the dependence of R&D Culture Index score on all sixteen available covariates was examined using multiple regression and regression tree modelling. RESULTS: There was a 54% response rate to the questionnaire. Primary healthcare professionals appeared to have an interest in and awareness of the importance of research in primary care but just 15% were found to be research active in this study. A more positive attitude towards an R&D culture was associated with having had previous research training, being currently involved in research and with not being a general practitioner (GP) (p < 0.001), but much variability in the R&D culture index score remained unexplained. CONCLUSION: Despite awareness of the importance of R&D in primary care and investment therein, primary healthcare professionals remain largely unengaged with the R&D process. This study highlights the issues that need to be addressed in order to encourage a shift towards a culture of R&D in primary care: lack of research training particularly in basic research skills and increased opportunities for research involvement. The use of the R&D Culture Index may enable groups to be identified that may be more research interested and can therefore be targeted in any future R&D strategy.